(untitled) (Journal of Civil Engineering Researchers, 2025)
Concrete is one of the most widely used construction materials globally; however, its production contributes significantly to carbon dioxide emissions. In the Middle East, annual date production is substantial, and date seeds, as a byproduct, are typically discarded. This study investigates three methods for incorporating date seeds into concrete: (1) Cement replacement: Using powdered date seeds (PDS) as a partial substitute for cement at 5%, 10%, 15%, and 20% levels; (2) Aggregate replacement: Replacing coarse aggregates with crushed date seeds (CDS) at 10%, 20%, and 30% ratios and (3) Hybrid approach: Combining PDS (0%, 5%, 10%, and 20%) with fly ash (fixed at 20%). Mechanical tests revealed that replacing cement with up to 10% PDS had no significant impact on compressive strength, whereas higher replacement levels reduced strength. Similarly, increasing the aggregate replacement percentage led to a decline in concrete strength. In contrast, the hybrid approach—combining PDS with 20% fly ash—enhanced compressive strength. Based on these findings, the third method emerged as the most effective for improving both the strength and sustainability of concrete. The optimized hybrid mixture was selected for further comprehensive evaluation, including tests for tensile strength, flexural strength, water absorption (porosity), sulfate resistance, and freeze-thaw durability. These assessments aimed to verify not only the mechanical properties but also the long-term durability of the modified concrete under diverse environmental conditions.